Kelimpahan dan keanekaragaman makrofauna tanah sebagai perekayasa kesuburan tanah pada penggunaan lahan yang berbeda di Kota Kendari - Darwis Suleman; Syamsu Alam; La Ode Rustam (Fakultas Pertanian Universitas Majalengka, 2025)
Land use patterns are prominent factors affecting the abundance and diversity of soil macrofauna and in turn affect structure and soil function. This study was carried out on farmers' land from October to December 2022. The study aims to evaluate the abundance, diversity and dominance as well as the richness of soil macrofauna on coconut and rambutan area and reeds field. Sampling for soil macrofauna used the monolith method and separation of macrofauna using hand sorting techniques. Monolith plots measuring of 20 x 20 cm with a depth of 20 cm were placed randomly for each land use with 3 replications. Data analysis was carried out on abundance, diversity and dominance of macrofauna as well as the taxon richness. Analysis of variance was also applied on the abundance and diversity of macrofauna. The results highlighted that the abundance and diversity of soil macrofauna was the highest in the reeds land in which the soil never been disturbed, followed by coconut and rambutan plantations. On the other hand, termite was dominance in coconut plantations by 82.30%, while earthworm was dominance in rambutan plantations by 64.36%. The current study concluded that the existence of soil macrofauna is a paramount important to be maintained as the main soil fertility engineer in agricultural land.